Air Quality at Sonamarg - A Tourist Hill Station in Kashmir Valley, India - R. Yousuf; Adil Hamid Sofi, Arshid Jehangir*, Naseer Ahmad Dar, A. (Journal of Experimental Sciences, 2011)
The present study was undertaken to determine the ambient air quality with respect to suspended particulate matter (TSPM), respirable suspended particulate matter (PM10), nitrogen dioxide (NO2) and sulphur dioxide (SO2) at Sonamarg- a tourist hill station in Kashmir valley. The ambient air quality at three different station namely Sonamarg town, Thajwas and Baltal was monitored from July to December in 2009. All the pollutants were measured with a sampling duration of 1 hour. The results showed high concentration of pollutants in summer months which correspond with peak tourist activity. The highest concentration of pollutants was recorded at Baltal site, while least values were observed at Thajwas site. TSPM and PM10 are chief air pollutants in the area, however, the values of NO2 and SO2 were well within the limits as set by EPA at all the sites. It can be concluded that tourist inflow, vehicular density, roadside dust, and burning of coal and fuelwood on a large scale are the main sources of air pollutants in this area.